2011
DOI: 10.1177/1010539511416223
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge About Sexually Transmitted Infections (STIs) and Attitudes Toward Female Sex Workers With STI Symptoms Among Health Care Providers in Laos

Abstract: This study aimed to assess the knowledge and attitudes among health care providers (HCPs) providing sexually transmitted infection (STI) service to female sex workers (FSWs). A cross-sectional survey was performed in 6 districts along Road 9, traversing Savannakhet province from Thailand to Vietnam. In total, 244 HCPs providing STI services were interviewed. In all, 54% of respondents had no STI training despite providing STI treatment. Misperceptions of STI causes, transmission routes, and symptoms were commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Health information delivered through HCPs may have difficulty reaching these women. This was also indicated in a previous study in the same district where HCPs had negative attitudes towards FSWs with STI symptoms, with many agreeing with the statement: "even if FSWs are counselled, they would continue to infect others" [10]. Innovative methods of providing STI information is needed in order to enhance women's access to the information they need.…”
Section: Discussionmentioning
confidence: 75%
“…Health information delivered through HCPs may have difficulty reaching these women. This was also indicated in a previous study in the same district where HCPs had negative attitudes towards FSWs with STI symptoms, with many agreeing with the statement: "even if FSWs are counselled, they would continue to infect others" [10]. Innovative methods of providing STI information is needed in order to enhance women's access to the information they need.…”
Section: Discussionmentioning
confidence: 75%
“…9 Health care provider stigma was often related to the assumption that beer promoters provide sexual services to their clients; similar populations of women seeking reproductive health care services, such as Lao sex workers, also experience stigmatizing attitudes from health care providers. 10 We undertook a study of access to reproductive health care services for internal migrant women who work as beer promoters in the Southeast Asian capitals of Bangkok, Thailand; Hanoi, Vietnam; Phnom Penh, Cambodia; and Vientiane, Laos. The complete study has been described elsewhere 11 ; this article will focus on the migrant beer promoters' experiences accessing health care at popular health care institutions in these 4 capital cities.…”
Section: Introductionmentioning
confidence: 99%
“…Due to perceived inappropriate behavior according to the Lao traditional culture, FSWs were previously put in rehabilitation camps called Don Nang or ‘womenâ€Čs island’ [8]. Although this is no longer practiced, studies have shown that FSWs in Laos are still perceived negatively and stigmatized, especially by healthcare providers (HCPs) [9]. Furthermore, seeking testing and treatment for STIs is hindered by high costs, long waiting times, and judgmental attitudes of HCPs [10].…”
Section: Introductionmentioning
confidence: 99%